Anti-androgenic mechanisms of Bisphenol A involve androgen receptor signaling pathway. (15th July 2017) - Wang, Hui; Ding, Zhen; Shi, Qiao-Mei; Ge, Xing; Wang, Heng-Xue; Li, Meng-Xue; Chen, Gang; Wang, Qi; Ju, Qiang; Zhang, Jin-Peng; Zhang, Mei-Rong; Xu, Li-Chun
Graphical abstract: The mechanisms responsible for AR antagonism of BPA involve inhibiting the AR N/C interaction and enhancing the interactions of AR-SMRT and AR-NCoR. BPA may interfere with the AR signaling to exhibit anti-androgenic activity. Highlights: BPA inhibits the mouse Sertoli cell TM4 cells proliferation. BPA inhibits AR amino- and carboxyl-terminal regions (N/C) interaction. BPA enhances the interaction between AR and SMRT. BPA enhances the interaction between AR and NCoR. Abstract: We have shown Bisphenol A (BPA) acts as an androgen receptor (AR) antagonist in the previous study. However, the mechanisms underlying anti-androgenic effects of BPA remain unclear. The objective of this study was to explore whether the AR signaling was involved in AR antagonism of BPA. The Cell Counting Kit-8 (CCK-8) assay and Real-Time Cell Analysis (RTCA) iCELLigence system were applied to analyze the mouse Sertoli cell TM4 proliferation. The mammalian two-hybrid assays were performed to investigate the effects of BPA on the AR amino- and carboxyl-terminal regions (N/C) interaction and the interactions of the AR with steroid receptor coactivator-1 (SRC-1), co-repressors including silencing mediator for thyroid hormone receptors (SMRT) and nuclear receptor co-repressor (NCoR). BPA exposure resulted in decreased TM4 cell proliferation. BPA inhibited the AR N/C interaction significantly. Furthermore, BPA enhanced the interactions of AR-SMRT and AR-NCoR significantly. In conclusion, these data suggest BPA inhibits Sertoli cell proliferation due to its anti-androgenic actions. The mechanisms responsible for AR antagonism of BPA involve inhibiting the AR N/C interaction and enhancing the interactions of AR-SMRT and AR-NCoR. The data uncover novel anti-androgenic mechanisms by which BPA antagonizes AR signaling, contributing to Sertoli cell proliferation suppression and male reproductive toxicology.